THE TECHNIQUE IN THE TRANSLATION OF ENGLISH INTO INDONESIAN ABSTRACTS - Heriyanti Novitasari (Corolla International Conference, 2022)
This reserach aims to investigate the types of translation techniques and to find out what translation techniques are commonly used in abstract translation. This research used qualitative research methods and descriptive research design. Data were taken from 6 abstracts from 3 educational journal articles. The 6 abstracts consist of 3 abstracts in English as the source language and 3 abstracts which have been translated into Indonesian as the target language. It was found that the translation techniques used in this study were transposition (14 data or 51.85%), amplification (4 data or 14.82%), borrowing (4 data or 14.82%), reduction (3 data or 11, 11%), and established equivalence (2 data or 7.40%). In addition, from this research, it was also found that the most frequently used translation technique is the transposition translation technique.